Four electron selective O2 reduction by a tetranuclear vanadium(IV/V)/hydroquinonate catalyst: application in the operation of Zn–air batteries - Keramidas, Anastasios D.; Hadjithoma, Sofia; Drouza, Chryssoula; Andrade, Tatiana Santos; Lianos, Panagiotis (My University, 2022)
The reduction of dioxygen plays a crucial role in both natural and artificial systems exhibiting peroxidase like activity, utilizing O2 as a cheap and green oxidant in several applications including the development of new effective sources of clean energy. The exploration of new facile and cost-efficient electrocatalysts which promote the interconversion between H2O and O2 remains a crucial challenge. In this work, the applicability of peroxidase mimicking tetranuclear vanadium(IV/V) hydroquinonate, 1, as a proton-coupled electron transfer (PCET) oxygen reduction electrocatalyst to metal-air batteries is presented. Cyclic and rotating disk voltammetry studies show that the O2 reduction is associated with the PCET mechanism. Measurements of the O2 consumption vs. pH reveal that two molecules of 1 reduce one molecule of O2 supporting a 4e- reduction of O2 to H2O. 51V NMR spectroscopy used for H2O2 trap experiments supports the 4e- reduction of O2. Exhaustive electrolysis shows that the redox reactions of 1 are fully reversible in the presence of O2. Compound 1 was used as a catalyst for the O2 reduction in a Zn-air battery. Aqueous solutions of the complex were transformed into gels by the addition of a small quantity of sulfuric acid. Then, the complex in the form of gel was easily deposited on a carbon cloth electrode and was directly applied for the construction and operation of a Zn-air battery. The presence of the complex resulted in a large increase of the current and the power produced by the cell, particularly in an acidic electrolyte where the complex operates the best. The application of the biomimetic complex 1 in the operation of metal-air batteries opens a new and interesting route for applying such molecules in a wide range of high importance technological applications.
Keywords: Zn–air battery; O2-reduction; PCET; Tetranuclear vanadium; Hydroquinonate